A Bibliometric Anaylysis Of Green Manufacturing Visualizing Network - Kumar, Raman; Singh, Sanjeet; Chohan, Jasgurpreet Singh (The journal of contemporary issues in business and government, 2021)
Green technologies issues have been receiving more attention in contemporary era of globalization. Nowadays, green manufacturing (GM) has become popular among manufacturing industries, especially in developing countries as it can assist in achieving higher performance of production industry. Bibliometric analysis on GM has been performed to explore the evidence based statistical comparison of published research in this domain. The present research is focused on presenting a bibliometric analysis of 461 manuscripts which were downloaded from Scopus database using the keyword “Green manufacturing” in article title. The comparative analysis of GM publication of three top countries i.e. China, India and US is presented. The visualized keywords analysis is performed using VOSviewer analytical tool for global trends as well as for Indian research scenario. The present work investigates the quantum of work performed by Indian researchers on different research concepts of green manufacturing using NVivo software. The outcomes of network analysis explore and justify the research gap in the field of green manufacturing.